Evaluation of QR Code Media in the Implementation of the Governor's SE Policy No. 4 of 2023 to Foreign Tourists - Agus Adi Sentana Putra; Luh Putu Mahyuni (Eduvest - Journal of Universal Studies, 2025)
This study examines the dissemination of policy information through QR Code Do's and Don'ts to foreign tourists in Badung Regency, Bali. The main issue is the high rate of rule violations by foreign tourists despite the policy’s implementation to control behavior during visits. The study aims to analyze the effectiveness of QR Codes as a public communication medium for conveying rules and to evaluate tourists’ responses to this information. Using a qualitative case study approach, primary data were collected through in-depth interviews with immigration officials, tourism agencies, public communication experts, and foreign tourists. Analysis was guided by Harold Lasswell’s Public Communication Strategy theory to understand the communication dynamics between the government as sender and tourists as recipients. Findings indicate that although the QR Code policy is implemented in multiple languages and supported by digital flyers and social media, the information delivery is ineffective in reaching all target audiences. Many tourists are either unaware of or do not scan the QR Codes due to unclear directions and inconsistent communication strategies. The study concludes that a re-evaluation is necessary, involving various stakeholders and combining conventional and digital media. This integrated approach can ensure the message is delivered comprehensively, improving tourists’ awareness and compliance with Bali’s rules.